Religion and Authority: The Role of Tuan Guru in Shaping the Islamic Discourse of Sasak Community in Lombok, West Nusa Tenggara, Indonesia - Moh Muhtador; Muhammad Said; Atika Ulfia Adlina (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2023)
Lombok’s religious characteristics evolved concurrently with Tuan Guru’s role as the primary knowledge source in the community. Tuan Guru plays a crucial religious role in domestic and public spheres, inspiring the Sasak people in Lombok. This article discusses Tuan Guru’s role in generating religious knowledge through power and authority. The paper explores the relationship between power and knowledge possessed by Tuan Guru, examining the growing Islamic discourse. It adopts a hysterographic study approach, analyzed through the genealogy of Michael Foucault’s theory of power and knowledge. This study aims to analyze and construct data from discourses, patterns, and public spaces related to the Tuan Guru phenomenon in Lombok. The findings highlight Tuan Guru’s pivotal role in disseminating Islamic teachings in Lombok society, showcasing his awareness of the authority in producing, influencing, and contributing to the development of Islamic style. This socio-religious scientific development study portrays Tuan Guru’s role in knowledge production, offering a significant development in understanding the Islamicity that has flourished not only in Lombok but possibly in other regions in Indonesia and the world.